The addiction of social media among the Gen Y personnel in Malaysian Qualifications Agency (MQA) / Hanisah Amran - Amran, Hanisah (2019)
The social media started as a divine gift to the human society, it was meant to enlighten the human society by connecting them and giving some other benefits like transferring knowledge, making available all the infonnation needed for human well-being, growth and prosperity. But as the social media becoming established and familiar to the people, it created its own set of problems. One of the key ones being social media. According to Dr. Jerald J. Block, from the Center for Internet Addiction, ~'social media addiction" affects as many as one in eight Americans. Block also defined social media addiction as a compulsive activity involving excessive use, withdrawal and negative repercussions including social isolation, lying, low achievement and fatigue. As the social media grows in Malaysia, social media addiction is surfacing as a key problem, particularly amongst the younger generation here. This research outlines a method to examine the level of social media addiction amongst Malaysian youth. The purpose of our study is to identify the use of social media among the Gen Y personnel in Malaysian Qualifications Agency (MQA) and the relation of excessive use to the addictive level. The researcher has devised an online survey to study the social media use among the Gen Y personnel in Malaysian Qualifications Agency (MQA). Apparently, the technology has the potential to hann or enhance the social skills and social life. Modem society has developed as autistic society. People tend to be more isolated even they are being surrounded by so much people around them. It can be said that there is lack of affective emotional contact with other people and there is tendency of insistence on sameness (keep on staring at their smart phone), abnonnality of speech (less talk) high levels of visuospatial skills or rote memory (Baruch, 2000). Phenomena such as the virtual organization and extending telecommuting might create an autistic society where people are detached from one another (Peiperl and Baruch, 2000). They stated that' 'one view is that the society that results from these new ways of working may be severely disabled when it comes to interpersonal communication: an "autistic society" in which we become unaccustomed to dealing with others except in purely transactional ways; a global village of poor communicators." At the end of the day, this can lead to loss of productivity in the workplace and employers need to develop policies in order to ensure that the employees are focus on their work during the office hour. Besides, the employers could enhance digital literacy and awareness in the workplace so that the employees could have some limit especially on the internet usage (social media to be specific).